Towards general network architecture design criteria for negative gas adsorption transitions in ultraporous frameworks - Krause, Simon; Evans, Jack D.; Bon, Volodymyr; Senkovska, Irena; Iacomi, Paul; Kolbe, Felicitas; Ehrling, Sebastian; Troschke, Erik; Getzschmann, Jürgen; Többens, Daniel M.; Franz, Alexandra; Wallacher, Dirk; et al. (Nature communications, 2019)
Switchable metal-organic frameworks (MOFs) have been proposed for various energy-related storage and separation applications, but the mechanistic understanding of adsorption-induced switching transitions is still at an early stage. Here we report critical design criteria for negative gas adsorption (NGA), a counterintuitive feature of pressure amplifying materials, hitherto uniquely observed in a highly porous framework compound (DUT-49). These criteria are derived by analysing the physical effects of micromechanics, pore size, interpenetration, adsorption enthalpies, and the pore filling mechanism using advanced in situ X-ray and neutron diffraction, NMR spectroscopy, and calorimetric techniques parallelised to adsorption for a series of six isoreticular networks. Aided by computational modelling, we identify DUT-50 as a new pressure amplifying material featuring distinct NGA transitions upon methane and argon adsorption. In situ neutron diffraction analysis of the methane (CD 4 ) adsorption sites at 111 K supported by grand canonical Monte Carlo simulations reveals a sudden population of the largest mesopore to be the critical filling step initiating structural contraction and NGA. In contrast, interpenetration leads to framework stiffening and specific pore volume reduction, both factors effectively suppressing NGA transitions. Porous framework material DUT-49 was recently demonstrated to exhibit a unique counterintuitive negative gas adsorption (NGA) behaviour. Here the authors identify framework DUT-50 as an additional pressure amplifying material that features distinct NGA transitions, and suggest structural design criteria to access other such materials.